If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -2y + 3z = 18 Solving 2x + -2y + 3z = 18 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2y' to each side of the equation. 2x + -2y + 2y + 3z = 18 + 2y Combine like terms: -2y + 2y = 0 2x + 0 + 3z = 18 + 2y 2x + 3z = 18 + 2y Add '-3z' to each side of the equation. 2x + 3z + -3z = 18 + 2y + -3z Combine like terms: 3z + -3z = 0 2x + 0 = 18 + 2y + -3z 2x = 18 + 2y + -3z Divide each side by '2'. x = 9 + y + -1.5z Simplifying x = 9 + y + -1.5z
| 6q-18=18 | | 9x^2+7=2 | | (72x-47y)-(63x+21y)= | | (49x+62y)-(21x-23y)= | | z/3-3=5 | | v-3/5=8.5 | | 1/5a=3.1 | | n/5+11=13 | | (12z^6-32z^6)/4z^2 | | C=400+15n | | (64x+56y)-(7x+38y)= | | 4(4x+14)+9x-17= | | X+7x/4=33 | | (9+3x)-3x= | | 3x-5(x+4)=-(x-7) | | 9(x-7)+14(x+10)= | | 4(2x+12)-6x= | | 7(6x+4)+5x= | | 7(t-3)+7t=7(2t+5)-12 | | 5(2x+6)-20= | | 2x^2-32x-72=0 | | (6x+16)-6= | | (55x+60y)-(10x-22y)= | | 7(5x+12)+13x-12= | | (63x+47y)-(3x-6y)= | | 1.6q-2.5-1.5q=-0.9q-3.3 | | =(-7)*10+5*10 | | (2x-x+9x^2)/(-1+3x) | | (w^2+10w+25)(w-2)=a+70 | | -8y+4=-9y+1 | | 2(x-5)+7=17 | | 35=x^2+x |